2011
DOI: 10.1051/0004-6361/201116872
|View full text |Cite
|
Sign up to set email alerts
|

TheHerschelVirgo Cluster Survey

Abstract: Context. Using Herschel data from the open time key project the Herschel Virgo Cluster Survey (HeViCS), we investigated the relationship between the metallicity gradients expressed by metal abundances in the gas phase as traced by the chemical composition of HII regions, and in the solid phase, as traced by the dust-to-gas mass ratio. Aims. We derived the radial gradient of the dust-to-gas mass ratio for all galaxies observed by HeViCS whose metallicity gradients are available in the literature. They are all l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
90
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 84 publications
11
90
1
Order By: Relevance
“…Each pixel was fitted with a single temperature modified black body, with dust emissivity κ ∝ ν β and β = 2; the filter response function was taken into account for the color correction. As shown by Davies et al (2012) for global fluxes, and by Magrini et al (2011) for pixel-by-pixel surface brightness analysis, our choice of the dust emissivity provides a satisfactory fit to the spectral energy distribution. If we exclude the notorious uncertainty of the dust emissivity, the uncertainties due to the fitting procedure amounts to 10-15% for the full depth HeViCS data set.…”
Section: The Sample and Ancillary Datamentioning
confidence: 67%
See 3 more Smart Citations
“…Each pixel was fitted with a single temperature modified black body, with dust emissivity κ ∝ ν β and β = 2; the filter response function was taken into account for the color correction. As shown by Davies et al (2012) for global fluxes, and by Magrini et al (2011) for pixel-by-pixel surface brightness analysis, our choice of the dust emissivity provides a satisfactory fit to the spectral energy distribution. If we exclude the notorious uncertainty of the dust emissivity, the uncertainties due to the fitting procedure amounts to 10-15% for the full depth HeViCS data set.…”
Section: The Sample and Ancillary Datamentioning
confidence: 67%
“…The dust surface mass density is derived as in Magrini et al (2011) (see also Smith et al 2010;Bendo et al 2010a). The five images in the Herschel photometric bands were convolved to the poorer resolution of the 500 μm, then registered on the same pixel grid.…”
Section: The Sample and Ancillary Datamentioning
confidence: 99%
See 2 more Smart Citations
“…These observational constraints include for instance the relation between dust mass and stellar mass (Corbelli et al 2012;Santini et al 2014), the gas fraction of galaxies and dust mass (Cortese et al 2012), dust mass and star-formation rate (SFR; da Cunha et al 2010;Casey 2012;Santini et al 2014), and the dust mass function of galaxies (Dunne, Eales & Edmunds 2003;Vlahakis, Dunne & Eales 2005;Dunne et al 2011;Eales et al 2009;Clemens et al 2013). Two particularly interesting scaling relations are the ratio between dust mass and gas mass in the ISM (dust-togas ratio; DTG), or the ratio between dust mass and the total mass in metals (dust-to-metal ratio; DTM) as a function of metallicity or galaxy stellar mass (Issa, MacLaren & Wolfendale 1990;Lisenfeld & Ferrara 1998;Hirashita, Tajiri & Kamaya 2002;James et al 2002;Hunt, Bianchi & Maiolino 2005;Draine et al 2007;Engelbracht et al 2008;Galametz et al 2011;Magrini et al 2011;Rémy-Ruyer et al 2014a). Rémy-Ruyer et al (2014a) demonstrated that the DTG ratio in galaxies cannot be described by a single powerlaw as a function of metallicity, but is better represented by a double power-law with a break around a metallicity of 0.1 Z (Edmunds 2001).…”
Section: Introductionmentioning
confidence: 99%